Dendritic-tumor cell immunohybridomas: from astroglial lysosomal fusion to treating prostate cancer - Zorec, Robert (Henry Stewart Talks, 2024)
Lysosome discovery and function, Reactive astrocytes, Measuring vesicle fusion, Lysosomal fusion in astrocytes, IFN-y induced antigen-presenting in astrocytes, Fusion pore regulation, Dendritic cells, Autologous Hybridoma Cells (aHyC), aHyC treatment for prostate cancer